Perancangan Ulang Tata Letak Pabrik Vulkanisir Ban - Merry Siska; Fachrul Sabri (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
The goals of designing factory layout is to decrease material handling from distance and cost.The problems occurred at PT. Pesona Laut Kuning is forming departement or machine which related toeach other but still apart that cause soar of distance material handling.Methods used by this research is simulation Arena, convetional techniques, and ALDEP. Afterdone processing with simulation, no need for replenishment machine because all stuff processed resolved.After data processing using conventional Techniques and ALDEP done then Alternative Optionsbe able to convetional techniques alternative 1 which one have the smallest distance and cost. Alternative1 convetional techniques can reduce 0,97 kilometer distance of material handling and save Rp.1.863.772,- per day which initially distance of material handling production floor 3,1 kilometer and cost ofmaterial handling Rp. 5.911.178,- after processing by convetional techniques, the distance of materialhandling is 2,2 kilometer and cost of material handling become Rp. 4.047.406,-.Keywords: ALDEP, conventional technique, material handling, plant layout, simulation